APLIKASI LAPORAN KEHADIRAN DOSEN DAN KARYAWAN STMIK PALANGKARAYA - Erfan, Muhammad (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2021)
Attendance is one of the benchmarks for employee development methods and related to attendance. STMIK Palangkaraya has used the Attendance Management System (AMS) application but the report format is not as needed. This study seeks to develop a web-based data bridge application to process attendance data for lecturers and employees. The research approach used is descriptive qualitative with eXtreme Programming as a system development method. The result of this research is an application that reports the attendance of lecturers and employees in a matter of hours and minutes as well as a detailed recapitulation per person. This application can be used as a component of performance appraisal.